A Crack in The Glass Ceiling: A Study on Promotion Bias to Top-Level Management Positions in Tacloban Academes - Michael Earl B. Castroverde (Intermestic: Journal of International Studies, 2018)
This research sought to determine whether the â€œglass ceilingâ€ still existed in one of the major working environments in Eastern Visayas, Tacloban City; as well as to gain insights on one of its causesâ€”ineffective Workforce Diversity Management. Semi-structured interviews were used to gather data with the Measures of Central Tendency used to ascertain its existence within a 10-year period in terms of (1) pay inequities between men and women and (2) frequency of women top-level managers. The research findings show that 1 out of 3 top-level managers in educational institutions in Tacloban, were women; with which 90% were positioned in lower-paying schools. The results suggest that this gender employment discrimination stems from the organizationsâ€™ approach to diversity. Of the four approaches, the most practiced were ignoring diversity and begin the process of dealing with diversity.